Tres nuevos registros para México de plantas acuáticas vasculares - Novelo R., Alejandro; Wiersema, John H. (Instituto de Ecología, A.C., 2000)
Bergia capensis L. (Elatinaceae), Eichhornia paniculata (Sprengel) Solms-Laub. (Pontederiaceae), and Nymphaea novogranatensis Wiersema (Nymphaeaceae), three species of aquatic vascular plants, are reported for the first time from Mexico, all of them growing in the Isthmus of Tehuantepec area, state of Oaxaca.